The conservation of phosphate-binding residues among PHT1 transporters suggests that distinct transport affinities are unlikely to result from differences in the phosphate-binding site. (19th October 2016) - Ceasar, S. Antony; Baker, Alison; Muench, Stephen P.; Ignacimuthu, S.; Baldwin, Stephen A.
Abstract : The plant PHosphate Transporter 1 (PHT1) family of membrane proteins belongs to the major facilitator super family and plays a major role in the acquisition of inorganic phosphate (Pi) from the soil and its transport within the plant. These transporters have been well characterized for expression patterns, localization, and in some cases affinity. Furthermore, the crystal structure of a high-affinity eukaryotic phosphate transporter from the fungus Piriformospora indica (PiPT) has revealed important information on the residues involved in Pi transport. Using multiple-sequence alignments and homology modelling, the phosphate-binding site residues were shown to be well conserved between all the plant PHT1 proteins, Saccharomyces cerevisiae PHO84 and PiPT. For example, Asp 324 in PiPT is conserved in the equivalent position in all plant PHT1 and yeast transporters analyzed, and this residue in ScPHO84 was shown by mutagenesis to be important for both the binding and transport of Pi. Moreover, Asp 45 and Asp 149, which are predicted to be involved in proton import, and Lys 459, which is putatively involved in Pi-binding, are all fully conserved in PHT1 and ScPHO84 transporters. The conserved nature of the residues that play a key role in Pi-binding and transport across the PHT1 family suggests that the differing Pi affinities of these transporters do not reside in differences in the Pi-binding site. Recent studies suggest that phosphate transporters could possess dual affinity and that post-translational modifications may be important in regulating affinity for phosphate.